2021
DOI: 10.1080/17445647.2021.1940325
|View full text |Cite
|
Sign up to set email alerts
|

Mapping cross-scale economic impacts of storm surge events: considerations for design and user testing

Abstract: Cartographic display of cross-scale phenomena and user-centered design are considered through a discussion of the development of an interactive web map depicting local-tonational economic impacts of hurricane storm surge events in Galveston Bay, Texas. Map development and design (as informed by stakeholder focus groups) is described, including approaches to presenting complex, cross-scale impacts of surge events across multiple years and scenarios. Particular consideration is given to how designs may communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…As our visualization demonstrates, Galveston has a complex flood hazardscape, with lower vulnerability in elevated areas near the seawall on the east end of the island and higher vulnerability on the bay side and west end. Consistent with earlier visualizations of Galveston flood scenarios with and without the Ike Dike (Retchless et al, 2021), our visualization shows that the Dike is likely to significantly reduce storm surge flooding -and associated property damage -in most areas of the island and for multiple storm surge and sea level rise scenarios. This could be especially beneficial to homes and businesses in low lying areas away from the sea wall that are currently at high risk of flooding during storm surge events without the protection of the Dike.…”
Section: Discussionsupporting
confidence: 88%
“…As our visualization demonstrates, Galveston has a complex flood hazardscape, with lower vulnerability in elevated areas near the seawall on the east end of the island and higher vulnerability on the bay side and west end. Consistent with earlier visualizations of Galveston flood scenarios with and without the Ike Dike (Retchless et al, 2021), our visualization shows that the Dike is likely to significantly reduce storm surge flooding -and associated property damage -in most areas of the island and for multiple storm surge and sea level rise scenarios. This could be especially beneficial to homes and businesses in low lying areas away from the sea wall that are currently at high risk of flooding during storm surge events without the protection of the Dike.…”
Section: Discussionsupporting
confidence: 88%
“…In one such effort, a research team studied how flood models may be combined with economic loss models to create interactive tools exploring scenarios for local to national economic impacts of a hurricane storm surge in Galveston Bay (Yildirim and Demir 2019). Results showed that the complexity and design of tools used to visualize the scenarios should be adaptable to the varying needs, expertise, and abilities of different user groups (Retchless et al 2021).…”
Section: Integrating Multi-agent Interactions For Coastal Risk Commun...mentioning
confidence: 99%
“…Similarly, VR coupled with urban simulation allows planners to interact with environments in an immersive, first-person view before designs are implemented. In the context of community adaptation planning, UDTs also provide important approaches for gaining deeper insights into community resilience through the simulation of multidimensional socioeconomic consequences of climate risk (Francisco, Mohammadi, and Taylor 2020; Ye et al 2021). Since UDTs often facilitate and incorporate these modeling, visualization, and simulation functions, we include these terms in our scoping review to help narrow our search results for UDT literature to articles that would be most likely to contribute to community infrastructure resilience.…”
Section: Scoping Review Of Udt Researchmentioning
confidence: 99%
See 1 more Smart Citation